Enhanced Expression of Mitochondrial Magmas Protein in Ovarian Carcinomas: Magmas Inhibition Facilitates Antitumour Effects, Signifying a Novel Approach for Ovarian Cancer Treatment - Ali Raza; Ashfaqul Hoque; Rodney Luwor; Ruth M. Escalona; Jason Kelly; Revati Sharma; Fadi Charchar; Simon Chu; Mary K. Short; Paul T. Jubinsky; George Kannourakis; Nuzhat Ahmed (Cells)
Mitochondrial-associated granulocyte macrophage colony-stimulating factor (Magmas) is a unique protein located in the inner membrane of mitochondria, with an active role in scavenging reactive oxygen species (ROS) in cellular systems. Ovarian cancer (OC), one of the deadliest gynaecological cancers, is characterised by genomic instability, affected by ROS production in the tumour microenvironment. This manuscript discusses the role of Magmas and efficacy of its novel small molecule inhibitor BT#9 in OC progression, metastasis, and chemoresistance. Magmas expression levels were significantly elevated in high-grade human OC compared to benign tumours by immunohistochemistry. The inhibition of Magmas by BT#9 enhanced ROS production and reduced mitochondrial membrane permeability, basal respiration, mitochondrial ATP production, and cellular functions, such as the proliferation and migration of OC cell lines in vitro. Oral administration of BT#9 in vivo significantly reduced tumour growth and spread and enhanced the survival of mice without having any effect on the peritoneal organs. These data suggest that Magmas is functionally important for OC growth and spread by affecting ROS levels and that the inhibition of Magmas activity by BT#9 may provide novel clinical benefits for patients with this malignancy.